1977
DOI: 10.1021/ja00465a020
|View full text |Cite
|
Sign up to set email alerts
|

An ion cyclotron resonance study of the structures of C7H7+ ions

Abstract: 7) F. P. Lossing. personal communication. The value of 156 kcai mol-' for AHf(CH&H=N+HZ) was derived from the AP of m l e 44 in the mass spectrum of (CH3)zCHNHz. We thank Dr. Lossing for his assistance in performing this measurement. (8) Values of 154 for AHf (CH3CH=N+HZ and CH3N+H=CHz reported by B. H. Solka and M. E. Russell, J. Phys. Chem., 78, 1268 (1974). (9) Values obtained from the proton affinities of NH3 and &CHzNH (207 and 220 kcal mol-l, respectively): I . The values for the heais of foimation of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 10 publications
4
39
1
Order By: Relevance
“…We take advantage of the fact that Bz + reacts with C 7 H 8 and Tr + does not. [25][26][27][28] The procedure has been described in detail previously. 25 Briefly, Ar + was injected into a helium buffer and allowed to react with C 7 H 8 .…”
Section: Methodsmentioning
confidence: 99%
“…We take advantage of the fact that Bz + reacts with C 7 H 8 and Tr + does not. [25][26][27][28] The procedure has been described in detail previously. 25 Briefly, Ar + was injected into a helium buffer and allowed to react with C 7 H 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Grubb and Meyerson, 22 from a study of the fragmentation of 13 C-and 2 H-labelled C 7 H 7 C ions derived from benzyl derivatives, concluded that the fragmenting ions had the symmetrical tropylium structure rather than the benzyl structure. More recent studies 23,24 of stable C 7 H 7 C ions derived from a variety of derivatives have concluded that both tropylium and benzyl ions are formed. These studies do not provide information on the structures formed at the appearance energy threshold; such information can be obtained for substituted C 7 ions from appearance energy measurements.…”
Section: Ionization and Appearance Energiesmentioning
confidence: 99%
“…Earlier studies focused on the structure of C 7 H 7 + products and the kinetics of the unimolecular dissociations. [1][2][3][4][5][6][7][8][9][10][11] Those reactions have been known to have two competing pathways [1][2][3][4][5][6][7][8][9] and the structures of C 7 H 7 + products have been known to be benzyl, tropylium, and tolyl cations. 5,6,[10][11][12][13] The widely accepted two channel mechanisms include direct C-X bond cleavage channel I leading to the formation of the tolyl ions and lower energy barrier channel II which leads to the formation of either the benzyl cations or tropylium cations or both.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Those reactions have been known to have two competing pathways [1][2][3][4][5][6][7][8][9] and the structures of C 7 H 7 + products have been known to be benzyl, tropylium, and tolyl cations. 5,6,[10][11][12][13] The widely accepted two channel mechanisms include direct C-X bond cleavage channel I leading to the formation of the tolyl ions and lower energy barrier channel II which leads to the formation of either the benzyl cations or tropylium cations or both. [1][2][3][4][5][6][7][8] However, the energetics and mechanisms of the structural rearrangements of C 7 H 7 + product ions following the formation of the ions have not been well established, [10][11][12][13] which has made it difficult to draw well-establish picture of the two-channel mechanisms even with such extensive experimental studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation